The Development of Audio Visual Learning Media in Improving Children’s Religious and Moral Values - Latifahanum Lubis; Khadijah Khadijah; Humaidah Br. Hasibuan (Jurnal Basicedu, 2022)
Morality and religion are the main fortresses for the formation of children's character in responding to the flow of globalization in the digital era. The form of concrete efforts is carried out through a quality learning process for children. This study aims to develop audio-visual learning media in improving the religious and moral values of early childhood. The author uses the type of research R&D (Research and Development). The use of this research method is intended to produce new products in learning and to test the effectiveness of these products. In this context, the product that will be produced is in the form of media in the form of the film "Aku Anak Salih" to improve religious and moral values for early childhood with the Borg and Gall model. The procedural stages include; data collection and preparation stage, product development stage, product validity stage, revision stage, product trial stage, dissimilation and implementation. The design of the media for the film "Aku Anak Salih" was carried out through determining the theme, making a logline, developing a film synopsis, making storyboards, and implementing the production system. The result is that the media is considered effective and valid by experts to be applied to students of RA Nurul Aflah, Medan Labuhan District. These media have advantages in terms of convenience that are presented to increase moral and religious values in early childhood, attract children's learning attention, and are in accordance with audio-visual learning styles. Likewise, there are weaknesses from this media in the form of a relatively long time in designing the media, demanding teacher creativity in designing technology-based media, and demanding adequate facilities in schools (projectors, sound systems, classrooms).